Scaling Model for Silicon Germanium Heterojunction Bipolar Transistor - Engelin Shintadewi Julian; Rudy S Wahjudi (Institute of Advanced Engineering and Science, 2015)
In the past half-century, scaling has been used to improve semiconductor devices performance. In this paper, we study the effects of scaling on SiGe(C) heterojunction bipolar transistors (HBTs) performances i.e. cutoff frequency (fT), maximum frequency of oscillation (fmax) and gate delay (τg). The SiGe HBT scaling models are developed from more than twenty years accumulated reported data. The results show that the peak cutoff frequency shows an increasing trend with emitter width scaling with a factor of WE-0.719, the peak maximum frequency of oscillation shows an increasing trend with emitter width scaling with a factor of WE-0.723 and the gate delay shows a decreasing trend with emitter width scaling with a factor of WE0.778. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7469